Capital intelectual de universidades federais brasileiras: influências isomórficas nas áreas de administração e planejamento - Donato, Edilaine Lovatto (2017)
This study aims to verify the influence of institutional isomorphism on Intellectual Capital in the areas of Administration and Planning of federal public universities, based on the perception of its managers. In the scope of university management, the Administration and Planning units play an important role, since the results of their activities influence all other areas of the uni- versities. In this context, the measurement of Intellectual Capital (IC) and its components (Hu- man, Structural and Relational Capital) enables strategies to be established, with attention to critical factors and positive increment, allowing the available resources to be exploited and generate value to the university. Understanding the effects of institutional isomorphism on prac- tices and behaviors also enables these effects to be managed in favor of universities. The liter- ature review was developed from the concepts of Bontis (1998, 1999) and Dias (2015) for the measurement of Intellectual Capital; And the concepts of DiMaggio and Powell (1983) for in- stitutional isomorphism and its coercive, mimetic, and normative origins. It is characterized as descriptive, performed through a survey or survey, with quantitative approach to the problem and data analysis through descriptive statistics and Structural Equation Modeling (PLS). The research universe encompassed all the Brazilian federal public universities, with a probabilistic sample and by adhesion. The data collection was carried out by the application of a question- naire directed to the maximum managers (Pro-Rectors) of the units and counted on the partici- pation of 44 universities, which represents 70% of the universe surveyed. The results confirm the findings of previous investigations and reinforce that there is a positive and significant re- lationship between the components of Intellectual Capital. As for the effects of isomorphism on the IC components, the results showed that coercive isomorphism influences Relational Cap- ital, and normative isomorphism influences Human Capital, both with positive and statistically significant results. In addition, based on the measurement of the Intellectual Capital of the Ad- ministration and Planning units, a general overview was created, presenting the results of the participating universities, to establish reference values and make comparisons possible. It is concluded that the measurement of Intellectual Capital available in the Administration and Planning units is important so that these resources can be managed and increased, and thus contribute to the improvement of the management and training of the Intellectual Capital of these units, which is reflected, therefore, in the performance and results of the entire university. For future research, it is suggested to carry out studies in the areas of finalist activities, to in- crease the knowledge about Intellectual Capital and to enable its management, as well as to understand the effects of external influences on the whole university.